2018
DOI: 10.3389/fphar.2018.00550
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Efficacy of Danhong Injection Combined With Percutaneous Coronary Intervention in Acute Coronary Syndrome: A Systematic Review and Meta-Analysis

Abstract: Background: Percutaneous coronary intervention (PCI) is widely used in treatment of acute coronary syndrome (ACS) clinically. It is believed that Danhong injection (DHI) extracted from salviae miltiorrhizae and flos carthami combined with PCI could increase the therapeutic efficacy on ACS. We provide an updated meta-analysis with detailed information on combination of DHI and PCI therapy.Materials and Methods: Electronic databases were searched for appropriate articles without language limitations on key words… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Compared with oral preparation, Danhong Injection has an advantage in taking rapid effect in the short time window of myocardial reperfusion. Systematic reviews have found that Danhong Injection is associated with improvement of reperfusion and LVEF, as well as reduction of MACE in acute coronary syndrome when combined with PCI [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with oral preparation, Danhong Injection has an advantage in taking rapid effect in the short time window of myocardial reperfusion. Systematic reviews have found that Danhong Injection is associated with improvement of reperfusion and LVEF, as well as reduction of MACE in acute coronary syndrome when combined with PCI [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review showed that Danhong Injection significantly reduced the risk of death and recurrent angina, arrhythmia, and heart failure and improved left ventricular ejection fraction (LVEF) and reperfusion in patients with AMI [20]. Compared with PCI alone, Danhong Injection combined with PCI can improve vascular endothelial function, reduce inflammation, and prevent platelet aggregation, suggesting that it may act on multiple pathological steps, improve myocardial microcirculation, and reduce reperfusion injury [21]. Several small-sample clinical trials demonstrated that Danhong Injection can reduce the occurrence of coronary no-reflow (Thrombolysis in Myocardial Infarction [TIMI] blood flow grade < 3 or corrected TIMI frame count >40s) in patients with MI and can promote postoperative microcirculation recovery (ST-segment resolution [STR] ≥ 70% or 50%) [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…DHI is a mixed extraction of Salvia miltiorrhiza (DS; Dan Shen; family: Lamiaceae) and Carthami Flos (HH; Hong Hua; family: Compositae /Asteraceae) [15][16][17]. DHI has been widely used as an important adjuvant for the treatment of cardiovascular and cerebrovascular diseases in China [14,18,19]. Even more importantly, a previous study demonstrated that DHI combined with conventional medicines could improve the electrocardiogram and reduce the symptoms of angina for the treatment of UA [20].…”
Section: Introductionmentioning
confidence: 99%
“…According to accumulated evidenced-based data, the combination of CHIs and WM is associated with considerable efficacy in treating patients with ACS ( Zhao et al, 2018 ). For example, a systematic review reported that Danhong injection (DH) could improve the therapeutic efficacy and reduce the incidence of MACE events in ACS patients after PCI ( Zou et al, 2018 ). Moreover, systematic reviews and meta-analysis studies shown that Sodium Tanshinone IIA Sulfonate injection (STS) and Danshenchuanxiongqin injection (DSCXQ) combined with WM appeared to be efficacious in the treatment UA ( Zhang et al, 2016 ; Tan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NMA can assist assessing and ranking the therapeutic effects of different treatments ( Rouse et al, 2017 ; Pan et al, 2019 ). However, at present, there are many systematic review studies on the adjuvant treatment of ACS with a certain type of DSCIs, lacking of comparison of efficacy between different types of DSCI ( Wu et al, 2015 ; Zhang et al, 2016 ; Wu et al, 2017 ; Tan et al, 2018 ; Zou et al, 2018 ). Therefore, the present research adopted NMA to explore the comparative effectiveness and safety between different DSCIs plus WM against ACS, providing a reference for clinical practice.…”
Section: Introductionmentioning
confidence: 99%